GL67 lipid-based liposomal formulation for efficient siRNA delivery into human lung cancer cells - Somayah J. Jarallah; Ahmad M. Aldossary; Essam A. Tawfik; Reem M. Altamimi; Wijdan K. Alsharif; Nouf M. Alzahrani; Homood M. As Sobeai; Wajhul Qamar; Ahmed J. Alfahad; Manal A. Alshabibi; Sarah H. Alqahtani; Abdullah A. Alshehri; et al. (Elsevier, 2023)
The efficient delivery of small interfering RNA (siRNA) to the targeted cells significantly affects the regulation of the overexpressed proteins involved in the progression of several genetic diseases. SiRNA molecules in naked form suffer from low internalization across the cell membrane, high susceptibility to degradation by nuclease enzyme and low stability, which hinder their efficacy. Therefore, there is an urge to develop a delivery system that can protect siRNA from degradation and facilitate their uptake across the cell membrane. In this study, the cationic lipid (GL67) was exploited, in addition to DC-Chol and DOPE lipids, to design an efficient liposomal nanocarrier for siRNA delivery. The physiochemical characterizations demonstrated that the molar ratio of 3:1 has proper particle size measurements from 144 nm to 332 nm and zeta potential of −9 mV to 47 mV that depends on the ratio of the GL67 in the liposomal formulation. Gel retardation assay exhibited that increasing the percentage of GL67 in the formulations has a good impact on the encapsulation efficiency compared to DC-Chol. The optimal formulations of the 3:1 M ratio also showed high metabolic activity against A549 cells following a 24 h cell exposure. Flow cytometry findings showed that the highest GL67 lipid ratio (100 % GL67 and 0 % DC-Chol) had the highest percentage of cellular uptake. The lipoplex nanocarriers based on GL67 lipid could potentially influence treating genetic diseases owing to the high internalization efficiency and safety profile.